2015
DOI: 10.1103/physrevc.91.055807
|View full text |Cite
|
Sign up to set email alerts
|

Nucleon self-energies for supernova equations of state

Abstract: Nucleon self-energies and interaction potentials in supernova (SN) matter, which are known to have an important effect on nucleosynthesis conditions in SN ejecta are investigated. Corresponding weak charged-current interaction rates with unbound nucleons that are consistent with existing SN equations of state (EOSs) are specified. The nucleon self-energies are made available online as electronic tables. The discussion is mostly restricted to relativistic mean-field models. In the first part of the article, the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
39
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(40 citation statements)
references
References 80 publications
(204 reference statements)
1
39
0
Order By: Relevance
“…In particular, our revised implementation of charged-current neutrinonucleon interactions (according to Ref. [23]) includes nucleon self-energy corrections [24][25][26][27]. We also account for differences in the weak-magnetism corrections of neutralcurrent neutrino-nucleon scatterings as in Ref.…”
Section: Numerical Setup and Simulated Modelsmentioning
confidence: 99%
“…In particular, our revised implementation of charged-current neutrinonucleon interactions (according to Ref. [23]) includes nucleon self-energy corrections [24][25][26][27]. We also account for differences in the weak-magnetism corrections of neutralcurrent neutrino-nucleon scatterings as in Ref.…”
Section: Numerical Setup and Simulated Modelsmentioning
confidence: 99%
“…In set3, electron neutrino pair annhilation into µ/τ neutrinos (set3a in Table 1) and µ/τ -neutrino scattering on electron (anti)neutrinos (set3b) (Buras et al 2003) is added to set1, respectively (see Appendices A and B for details). In set4a, medium modification to electron(/positron) capture reactions on proton(/neutron) are taken into account Roberts et al 2012;Hempel 2015;Roberts & Reddy 2017) at the mean-field level (Reddy et al 1998) (see Section 3.4). Set4b includes medium dependent suppresion of Bremsstrahlung (Fischer (2016), their Equation (11)).…”
Section: Neutrino Opacitiesmentioning
confidence: 99%
“…The results showed that the experimental data significantly constrain the calculations. This work was extended to include all light particle species and more detail on the interaction, Coulomb effects and particle degrees of freedom [15]. These proceedings are, in part, a summary of that work.…”
Section: Introductionmentioning
confidence: 99%